Keanekaragaman Tanaman Kantong Semar (Nepenthes spp.) di UIN SUSKA Riau Pitcher Plant (Nepenthes spp) Diversity in the UIN SUSKA RIAU - Rosmaina Rosmaina; Zulfahmi Zulfahmi; Rizka Rosa (Jurnal Agroteknologi, 2012)
Forest of the UIN SUSKA Riau was harboring most of the genetic resources, one of them is pitcher plants (Nepenthes spp). Pitcher plants have high economic value because of they were ornamental and medicinal plants. This research aims to determine population density, diversity index, evenness index and dominance index of Nepenthes in the campus forest of UIN SUSKA Riau. This research used method was purposive sampling with square Jalur method. The result of this study found two species of Nepenthes in the campus of UIN SUSKA Riau, namely Nepenthes gracillis and Nepenthes ampularia. The average of population density of Nepenthes gracillis and Nepenthes ampularia were 2000 individuals/ha and 200 individuals/ha, respectively. The Diversity index of Nepenthes in this study was low (H’ <1), while average of evenness index (E) of Nepenthes was 0.352.